Analisis Peramalan dengan Metode Moving Average dan Exponential Smoothing dalam Perencanaan dan Pengendalian Produksi Pabrik Tempe Jombang - Jorgi, Bernard; Kusumawati, Aulia; Prabowo, Zaki Agung; Hamdani, Mohamad; Gandhi, I Gusti Putu Setya; Nugraha, Ahmad Reza (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Production planning and control are essential aspects in ensuring smooth production processes, creating profitable products, and making sure products are available on time. The home industry for tempeh production located in Link. Jombang Kali, Jombang District, has been operating since 1993 and continues to this day. However, this tempeh factory often experiences fluctuations in production, including both overproduction and underproduction. Therefore, a study was conducted to evaluate and forecast the production levels for upcoming periods. Forecasting errors were evaluated using Mean Absolute Deviation (MAD), Mean Squared Error (MSE), and Mean Absolute Percent Error (MAPE). The purpose of this study is to compare the Moving Average and Exponential Smoothing methods. The results of the analysis show that the Exponential Smoothing method produces lower error values, with MAD of 387.163, MSE of 261,914.1, and MAPE of 0.055349, compared to the Moving Average method.